Low cycle fatigue of thin-wall printed Onyx in energy absorption - Moises Jimenez-Martinez; Guillermo Narvaez; Paulina Diaz-Montiel (Heliyon)
Passive safety systems have been evaluated for their ability to transform impact energy into deformation to reduce the probability of damage to passengers during crash events. Low-speed impacts are common during collisions and many structural components are not replaced after such collisions because of the recovery of visual components such as the bumper fascia. However, automotive foams and brackets deform permanently in case a new impact fails to dissipate energy. In this study, a thin-walled printed Onyx component was fabricated via additive manufacturing. This material was used to dissipate energy at low-cycle fatigue and recovery in the peak crushing force after the first crushing cycle. The thin-wall crash box printed with Onyx, can be designed to recover energy absorption in different regions of the crushing displacement. The first peak crushing force and the mean crushing force are recovered according to the geometry and small displacements. However, in medium and long crushing displacements, at the end of the compression its dissipation capacity is increased. Onyx printed mechanical absorber withstand fifteen load cycles, recovering the peak load 19.25%.